KONSTRUKSI KEBENARAN HAKIKI DALAM EPISTEMOLOGI BAYĀNĪ, ‘IRFĀNĪ DAN BURHĀNĪ ‘ĀBID AL-JĀBIRĪ - Taufiq, Muhammad (Jurnal Studi Islam dan Sosial, 2025)
This paper outlines the bayānī, ‘irfānī, and burhānī epistemologies that are part of ’Ābid Al-Jābirī’s project to critique Arabic reason. This research aims to explain the construction of truth based on the three systems of thought in the Arab-Islamic world and see its relevance in the present. This research is qualitative research with a type of literature that aims to produce information from various sources. The results indicate that the truth in bayānī epistemology comes from religious texts such as the Qur'an and Hadith using a linguistic approach. The truth in ‘irfānī epistemology is obtained from direct experience God bestows through intuition using spiritual cultivation. The truth in burhānī epistemology comes from the reality obtained through human intellectual abilities through senses, experiments, and logical rules. The synergy of the three epistemologies will form a tradition of critical thinking, empirically based knowledge, and deep spiritual understanding.